A mudança, a resistência e a persistência dos técnicos do NEPI de um ex- distrito de saúde do município de São Paulo Change, resistence and perseverance of NEPI's technicals in a health district of São Paulo city - Lourdes Bernadete dos S. P. Alexandre; Maria Josefina Leuba Salum (Universidade de São Paulo, 1998)
O trabalho tomou como objeto de estudo o trajeto dos Núcleos de Epidemiologia Pesquisa e Informação (NEPI) do antigo Distrito de Saúde Tucuruvi/ Jaçanã, período 1991-1996. Adotou como referência a categoria modelo tecno-assistencial, reconhecendo o objeto de estudo na relação dos sujeitos sociais com a gestão pública e desdobramentos na saúde e com os saberes/práticas nucleares inscritos na realidade estudada. Dois projetos políticos distintos nutriram a trajetória dos NEPIs. Os NEPIs nasceram, em 1991, na gestão Erundina, sob a experiência da distritalizaçâo. Cresceram, até 1993, em torno de experiências fundadas nas tradicionais atividades de vigilância epidemiológica na perspectiva de transitar para a vigilância à saúde. A interrupção formal da municipalização, no início da gestão Maluf, não foi suficiente para desviar a rota de estruturação dos NEPIs. Sobreviveram até 1996, resguardados pelos conteúdos e práticas construídos na gestão anterior. Mesmo limitados rumo à implantação da vigilância à saúde, aperfeiçoaram-se no processamento da informação, mantendo minimamente as atividades clássicas de Vigilância Epidemiológica. As evidências deste trajeto de "sobrevivência" estão demarcadas na Instrução Normativa 003/96, publicada no final da gestão Maluf, que privilegia atividades iniciadas na gestão Erundina. A trajetória destes NEPIs foi inquestionavelmente estruturada pela mudança e resistência de todos e de cada um. No limite de suas forças, ainda que por vezes confusos, mantiveram-se coesos e, num movimento de reação coletiva, não se frtaram a integrar "um novo modo de pensar e agir em saúde". The object of this work is the trajectory of the Research and Information Centers (NEPI) of the extinct Health Districts Tucuruvi/Jaçanã of the Municipal Office of Health of São Paulo City, between 1991 and 1996. The theoretical reference is the techno-assistencial model. The analysis concerned: the relationship between social actors and public administration; the consequences of this relationship to the health domain (political dimension) and finally the relationship between these social actors and the health nuclear knowledge and practices (technological domain). This process allowed the search for the "constitutive heterogeneity" between empirical and theoretical data. The analysis shows that two distinct projects have nurtured the NEPIs trajectories. They were originated under the influence of an Italian cooperation and the Sanitary Reform principles; the political project of the new Brazilian Unified Health System (SUS); and the health "territorialization" information system. The NEPIs grew until 1993 developing epidemiological traditional surveillance trying to broaden their activities. After 1993, under another municipal administration, the "territorialization" process was interrupted and the public health sector was conducted by the mercantilist logics of the World Bank. This was not sufficient to deviate the original route. The NEPIs survived until 1996 inspired by the contents and practices built in the former administration. Although they were limited in their intent to amplify health surveillance, the information system was improved and all the efforts were made to maintain the surveillance activities. The relationship between social actors and the distinct public administration projects has organized the NEPIs trajectory at the cost of collective and individual changes. To the limits of their resistance, these social actors have faced political adversities reacting collectively to the point of developing a "new way of thinking and acting in health".